The impact of monitoring tool improvements on workplace stress, job satisfaction and job performance: An IAR study in RMLG of LBP - Zarate, Zandra Ohira C. (Animo Repository, 2022)
The purpose of this Insider Action Research is to improve work-related stress management through the creation of a standard monitoring tool. In essence, the focal issue we have identified is the stressors that are affecting the employee’s performance. Concerns raised during the initial discussions were (a) pressure on account monitoring, (b) target accomplishments, (c) reports preparations, (d) overloaded teams, (e) team partner work relationships, (f) age or generation gap, (g) department head that is doing micro-management to those performers while a little loose with the non-performing teams thus creating a silent gap between the performers and the non-performers, among others. Although the issues identified were all work-related, they geared towards personal differences of the personnel that affects their portfolio management style. With this consideration, the proposal focused on how to lessen work-related stress in the workplace towards employee empowerment that would redound to improved performance. In the first cycle, we have prepared a standard excel file to monitor the team’s portfolio. We maximized mini-programs in the excel file for the notifications for the transactions. Meanwhile, the same was discussed with our Technology Management Group (TMG), so we can plan what the program will look like. During the last part of the first cycle, our TMG created a simple database of basic information or the Retail and Mid-Market Lending Group – Monitoring Tool (RMLG – MT). During the second cycle, we discussed in detail the enhancements to be implemented, it was further broken down into three phases so that we can have small wins and so we can immediately use the tool. Here, we introduced “The Five Conversation Framework”, where there are five themes or key points: climate review, strengths and talents, opportunities for growth, learning and development, and innovation and continuous improvement. All five themes encourage superior subordinates’ cooperation to attain a healthy working environment. It innovates the traditional performance review to a more employee-centered assessment and evaluation. This supports the framework used in identifying stress in the workplace. And it was concluded that when management’s concept that if the health of employees and leadership practices in the workplace intertwine, it clarifies the relevance of good well-being in the organization. Thus, using the holistic approach where both the bank and the employees will benefit. This Insider Action Research (IAR) discusses ways undertaken to improve the efficiency of Account Management in the Retail and Mid-Market Lending Group (RMLG) under the Agricultural & Development Lending Sector (ADLS), then, now National Development Lending Sector (NDLS) of Landbank of the Philippines (LBP). In a broader context, other lending centers of the Bank could use this action research as a reference in creating an efficient and effective monitoring tool by placing importance on usability, data sharing, and accessibility to improve efficient account monitoring and management. Keywords: Stress Management, Lending, Account Monitoring, Portfolio Management, Database, Action Research, Job Satisfaction, Improved Performance